OBSTETRIC VIOLENCE: ANALYSIS FROM THE PERSPECTIVE OF CYBERFEMINISM AND THE PROJECTS OF LAW IN PROGRESS IN BRAZIL - Letícia Demétrio, Amanda; Brustolin, Alessandra (Revista Gênero e Interdisciplinaridade, 2022)
The work approaches the lack of legislation to regulate acts of obstetric violence. The analysis is carried out from the perspective of the demands of the cyberfeminist movement in Brazil. Therefore, the research consists of verifying whether the Bills in Process in Brazil from 2015 to 2021 meet the requirements of cyberfeminism. For the analysis, specific criteria were determined, based on the understanding of the movement. The demands of cyberfeminism point to the need for a conception of obstetric violence, in legal documents that define and criminalize it, which will help in identifying and holding the driver responsible, in addition to public policies in favor of restraint. Therefore, it was possible to see that most of the Projects partially meet the requirements of cyberfeminism, and it is possible to note that law project No. 878/2019 is the one that best suits the specificities of the movement.